Investigating the Impact of Office Smartization Indicators on the Quality of Financial Processes in Governmental Organizations - Shahbazi, Fartash; Ferdosipour, Lili; Montazeri, Mohammad (Business, Marketing, and Finance Open, 2025)
This study examines the impact of office smartization indicators on the quality of financial processes in governmental organizations. In terms of purpose, the research is categorized as applied research and, among descriptive methodologies, it is conducted as a case study. The statistical population consisted of employees working in governmental organizations with an unlimited population size, and based on Cochran’s formula, a sample of 384 respondents was determined. Following the assessment of variable distribution and descriptive analysis, structural equation modeling was performed using Smart PLS software, and statistical tests were conducted in SPSS. Given that all research hypotheses were confirmed, it can be concluded that office smartization has a significant and positive effect on improving the quality of financial processes in governmental organizations. The utilization of smart technologies, decision support systems, data analytics, and administrative automation enhances accuracy, transparency, speed, and efficiency in performing financial activities. It is recommended that managers, through active engagement with supervisory and regulatory institutions, take steps toward clarifying and updating financial regulations in order to establish a foundation for intelligent decision-making and stable, accountable financial processes.